已知x=-1⼀2,求4(x+1)^2-7(x-1)(x+1)+3(1-x)^2的值

2025-02-24 17:58:18
推荐回答(4个)
回答1:

4(x+1)^2-7(x-1)(x+1)+3(1-x)^2
=4(x²+2x+1)-7(x²-1)+3(x²-2x+1)
=8x+4+7-6x+3
=2x+14
=2*(-1/2)+14
=13

回答2:

4(x+1)^2-7(x-1)(x+1)+3(1-x)^2
=4(x+1)^2-7(x-1)(x+1)+3(x-1)^2
=[(x+1)-(x-1)][4(x+1)-3(x-1)]
=2(4x+4-3x+3)
=2(x+7)

(x+1/2)^2=0
x+1/2=0
x=-1/2

原式=2×(-1/2+7)
=2×13/2
=13

回答3:

4(x+1)^2-7(x-1)(x+1)+3(1-x)^2
设x+1=a,1-x=b,则a=1/2,b=3/2原式变为
4a²+7ab+3b²=(4a+3b)(a+b)=13

回答4:

式子化简得:4x^2+8x+4-7x^2+7+3-6x+3x^2=2x+14
把x代入得 2*(-1/2)+14=13